Artificial Intelligence and Machine Learning for Multi-Domain Operations Applications 2019
DOI: 10.1117/12.2518644
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual architecture for contractual data sharing in a decentralised environment

Abstract: Machine Learning systems rely on data for training, input and ongoing feedback and validation. Data in the field can come from varied sources, often anonymous or unknown to the ultimate users of the data. Whenever data is sourced and used, its consumers need assurance that the data accuracy is as described, that the data has been obtained legitimately, and they need to understand the terms under which the data is made available so that they can honour them. Similarly, suppliers of data require assurances that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In previous work, 30 the authors have proposed a model of a supply chain for AI/ML products, based on the premise of ML model authors and publishers populating a BOM document that provides details of the contributions of components, such as data sources and other artifacts, along with the human work toward creation of the resultant ML model. Describing ML systems in terms of their supply chain provides a mechanism to identify data sources and assets which contribute to the development of these data components.…”
Section: Related Workmentioning
confidence: 99%
“…In previous work, 30 the authors have proposed a model of a supply chain for AI/ML products, based on the premise of ML model authors and publishers populating a BOM document that provides details of the contributions of components, such as data sources and other artifacts, along with the human work toward creation of the resultant ML model. Describing ML systems in terms of their supply chain provides a mechanism to identify data sources and assets which contribute to the development of these data components.…”
Section: Related Workmentioning
confidence: 99%
“…Future research will attempt to identify a set of objective measures that will be capable of being mechanised to replace the subjective elements of the ranking. A Bill of Materials document supplied or made available with the model, as proposed 43 , would be a suitable vehicle for making such information about the contributors available to model users, as it facilitates both the identification of significant contributions to the system (the nodes) as well as providing a means to identify supporting information and artifacts. Other proposals for documentation of ML systems, such as the Model Card proposal from Mitchell et al 27 or a Supplier's Declaration of Conformity as suggested by Hind, et al 30 , could also be used as the basis for a framework which delivers information from which the visibility judgements could be made.…”
Section: Score Quantitymentioning
confidence: 99%
“…Future research will attempt to identify a set of objective measures that will be capable of being mechanised to replaces the subjective elements of the ranking. A Bill of Materials document supplied or made available with the model, as proposed [2], would be a suitable vehicle for making such information about the contributors available to model users, as it facilitates both the identification of significant contributions to the system (the nodes) as well as providing a means to identify supporting information and artifacts. Other proposals for documentation of ML systems, such as the Model Card proposal from Mitchell et al [19] or a Supplier's Declaration of Conformity as suggested by Hind, et al [20], could also be used to provide information from which the visibility judgements could be made.…”
Section: Quantifying Supply Chain Visibilitymentioning
confidence: 99%
“…In considering the development pipelines for ML models we can identify the contributing assets, which will typically include data sets used for training and validation, and human expertise which is used both in the preparation and curation of training data, and in the development and calibration of the resultant model. In previous work [1], [2] we have considered the benefits of applying established techniques from industry and agri-food to provide transparency and traceability on contributions to data products created through the aggregation of multiple machine and human input sources, including supply chain modelling (SCM) and the maintenance of a Bill of Materials (BoM) document to clearly identify the contributors to the output products of data ecosystems and machine learning pipelines.…”
Section: Introductionmentioning
confidence: 99%